Localibras: uma aplicação para localização e divulgação de sinais de lugares na UFPA - PIMENTEL, Samara Fernandes (2019)
The Brazilian sign language Libras is considered the country's second official language, but is not known by many of the hearing people. Although they are located at the same territory, Libras and the Brazilian Portuguese Language have completely different communication channels, what makes them dissimilar from each other. This directly affects the communication between deaf people and hearing people who don't know sign language. It is important to remember that today the exist applications are geared towards translation between these two languages, not considering the regionalization and no focusing on the deaf people's help to obtain their independence. This paper presents a multiplatform application that seeks to assist the deaf people to identify points and tracing routes within the Federal University of Pará, also promoting the specific signs of these places. In order to obtain relevant results, it was used an automated test and an evaluation with observation and interviews with people who understand Libras, even if they can hear or not. The obtained results at the automated teste had 100% compatibility with varied Android’s version, and at the evaluations of the users were found eight main problems that served to known possible improvements to incorporate in the application’s current version.